Gender in an urban world - DeSena, Judith N. (Bingley, UK : Emerald JAI, 2008)
This volume, "Gender in an Urban World," brings the analysis of gender from the margin to the center of urban theory. "Gender in an Urban World" examines the influence of gender in shaping relations in urban spaces and places. It represents a "crack" in the landscape of urban sociology, and engages in the discourse of the field from a gendered perspective. This volume is global in focus and includes empirical and field studies as it relates to structure, politics, policy and everyday life within an urban context.The authors investigate the ways in which the urban world is gendered, and the roles of womens and mens agency in creating and changing urban life. Reconceptualizations of various models, focusing on local, metropolitan, and international environments are also included. "Gender in an Urban World" contributes innovative theoretical paradigms to the urban field. It is meant to contribute to an ongoing dialogue with regard to gender within the context of urbanism and urbanization. It includes chapters authored by leading experts from around the world. It brings the analysis of gender from the margin to the center of urban theory.
Includes bibliographical references.
Description based on print version record.
Keywords: Women -- Social conditions; Sociology, Urban; Gender studies, gender groups; Social Science -- Gender Studies; Social Science -- Sociology -- Urban